(untitled) (UUM Journal of Legal Studies, 2024)
The acceptance of Freedom of Information (FOI) as a fundamental mechanism for enhancing accountability and transparency in the public sector is widely recognized. Numerous international legal instruments (Conventions) have advocated for the establishment and enforcement of legal frameworks pertaining to the FOI. The FOI legislation serves two essential functions, namely enhancing democratic engagement and mitigating corruption within the public sphere. Despite the acceptability of FOI on the global stage, Malaysia lacks a comprehensive legal framework to address the right to access information, except for Selangor and Penang. Additionally, there are various national legislations that hinder the exercise of FOI. This article’s objective is to examine the use of the FOI concept within the framework of international legal instruments as well as the challenges posed by Malaysian national laws that impose limitations on its implementation. The objective is achieved by employing a doctrinal methodology that incorporates international legal instruments as well as Malaysia’s legislations (Constitution, Acts and Enactments) pertaining to the FOI. The findings show the restrictions under national law make it difficult to implement FOI legal regimes in Malaysia. This paper argues that implementing FOI can only be materialized through a comprehensive review of existing laws and administrative structure reform by adapting universal standards on FOI as stated under international legal instruments. This article serves as guidelines for policymakers intending to address FOI as the anti-corruption mechanism in public sectors. Moreover, recommendations are made for the implementation of FOI into Malaysia’s domestic laws.